Frontiers in neurosurgery. - Peschillo, Simone (Frontiers in Neurosurgery., 2015)
Frontiers in Neurosurgery is an eBook series which triggers principle issues that still fuel debate in neurosurgery. The series is intended as a reference for practicing endovascular neurosurgeons, vascular neurosurgeons, interventional neurologists and neuroradiologists who have a solid knowledge of neuroangiography.